Foreign Relations Law on Treaty Matters from Restatement (Third) to Restatement (Fourth): More a Filter Than a Bridge. (22nd January 2022) - Miron, Alina; Palchetti, Paolo
Abstract: The remarks contained in this article are a candid reading of Part III of the Restatement of the Law (Fourth): Foreign Relations Law of the United States ('Treaties as Law of the United States') through the lens of international lawyers who wonder about the role of international law in the US legal system. They turn essentially on the promise and peril of domesticating international law: Does foreign relations law as determined by Part III the Restatement (Fourth) promote compliance with international treaty law or does it rather emphasize constitutional law concerns that may limit its domestic application? To what extent do domestic judicial authorities give effect to treaties at the domestic level? Is the question of the self-executing character of a treaty provision exclusively a matter of domestic law or does it depend also on treaty interpretation? Our conclusion is that, on treaties, the Restatement (Fourth) marks a retreat in the engagement with international law from the Restatement (Third) .